(untitled) (Indian Journal of Traditional Knowledge (IJTK), 2023)
Being one of the most sought-after crops as a cut flower for borders, decoration and display, gladiolus is in high demand among flower lovers. In order to boost planting of freshly harvested corms which is hindered by presence of dormancy, several herbal extracts have been investigated on different varieties of gladiolus along with the commercially used chemical GA3. Among all the treatments, Azadirachta indica (Neem) extract at 2% came out as most effective treatment in improving corm sprouting parameters and was also found to be statistically at par with GA3 at 100 ppm. Among varieties, V2 (Morning Gold) was found to be most responsive variety under the effect of herbal extracts. Through this study it was indicated that natural plant products which are environmentally sound and safe to use can be used as alternatives to chemicals used in breaking the dormancy of gladiolus and expanding its limits of cultivation.